A framework for analyzing the competitiveness of unconventional modes of transportation in developing cities. (July 2020) - Sobhani, Md. Golam; Imtiyaz, Md. Nafis; Azam, Md. Shafiul; Hossain, Moinul
Highlights: A framework for assessing competitiveness of unconventional modes (UCM) of transport. Fusions PESTLE qualitative framework with AHP-TOPSIS based quantitative methods. Modes compared include: Rickshaw, Easy Bike and Leguna. Standings of competitiveness in order: Rickshaw, Easy Bike and Leguna. Findings help in design conventional public transport and integration of UCM. Abstract: Unconventional modes of transport (UCMs) play a substantial role in many developing cities in meeting the mobility demand in spite of having negative image in the eyes of the authorities. This manuscript outlines a conjoint framework where various factors affecting sustainability and competitiveness of UCMs are identified through observation study and organized using PESTLE qualitative framework. Afterwards, it presents an AHP-TOPSIS based qualitative approach where inputs from experts as well as major stakeholders (owners/operators, drivers, conductors and passengers) are combined based on the PESTLE framework to fathom the competitiveness of UCMs. Along this process, the manuscript also unveils the business model of UCMs along with their area of operation, advantages and weaknesses. For this, the study uses Dhaka, the capital city of Bangladesh as study area and selects three popular UCMs – locally known as Rickshaw, Easy bike and Leguna. The findings suggest that economic, social and political factors respectively have the highest influence among all factors of PESTLE. Rickshaw was found to be the most competitive followed by Easy bike and Leguna. The study is expected to shed light into the perception and expectation of major stakeholders of UCMs which in turn will provide valuable insight for designing conventional public transport services, and/or, help in slowly integrating the UCMs into the mainstream transportation service through addressing their shortcomings.